Decree no. 861 of the year 2005 Issuing The Executive Regulations of The Law On Organizing Customs Exemptions = اللائحة التنفيذية لقانون الإعفاءات الجمركية (2025)
Decree No. 861 of the year 2005 issuing the executive regulations of the law on organizing customs exemptions – the executive regulations of the law on organizing customs exemptions وزارة المالية قرار رقم 861 لسنة 2005 بإصدار اللائحة التنفيذية لقانون تنظيم الإعفاءات الجمركية – اللائحة التنفيذية لقانون تنظيم الإعفاءات الجمركية